Hugh Pine and the good place - Van de Wetering, Janwillem, 1931-2008 (Houghton Mifflin, 1986)
Hugh Pine, a porcupine, decides to live alone on an island in order to get away from all the problems the forest animals bring to him; but after a time he decides being alone isn't so wonderful after all.